О построении основ механики разрушения материалов при сжатии вдоль трещин (обзор) - Гузь, А.Н. (Прикладная механика, 2014)
Проаналізовано основні результати щодо створення основ механіки руйнування матеріалів при стиску вздовж тріщин в однорідних матеріалах з тріщинами та в неоднорідних (композитних) матеріалах з тріщинами на границях розділу. Розглянуто результати, які одержано в рамках пружних, пластичних та в’язкопружних моделей деформівних тіл. Оглядова стаття складається з трьох частин. An analysis of the main results on construction of the foundations of the fracture mechanics of materials in case of compression along cracks as applied to the homogeneous materials with cracks and inhomogeneous (composite layered) materials with interface cracks is presented. The results are considered which are obtained in the framework of elastic, plastic and visco-elastic models of deformable bodies. This review article consists of three parts.